2013
DOI: 10.5539/jfr.v2n2p83
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Essential Minerals from Staples Commonly Consumed in the Tropics

Abstract: This study assessed essential minerals in sweet cassava (Manihot esculenta), Lucea yam (Dioscorea rotundata), plantain (Musa sp.) and pumpkin (Cucurbita pepo) by atomic absorption spectrophotometry while mineral bioavailabilities were assessed by in vitro enzymatic digestion.Undigested cassava samples displayed highest calcium concentrations (3150 ± 320 mg/Kg) while the highest iron concentrations were recorded in pumpkin samples (81.5 ± 4.7 mg/Kg). Magnesium concentrations were highest in ripe plantain sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…First domesticated in neo-tropical lowland South America 8,000–10,000 years ago, cassava continues to be a dietary staple across this region for many Amazonian forager-horticulturalist groups ( Piperno, 2011 ). Fermented cassava beer remains a key component of the diet for many, with fermentation improving bioavailability and synthesis of essential vitamins and minerals (zinc, calcium, iron and magnesium) that may otherwise be lacking ( Boonnop et al, 2009 ; Ahaotu, Ogueke & Owuamanam, 2011 ; Dilworth, Brown & Asemota, 2013 ). This is particularly important since chronic nutritional stress among indigenous groups can stunt growth ( Blackwell et al, 2009 ; Piperata et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…First domesticated in neo-tropical lowland South America 8,000–10,000 years ago, cassava continues to be a dietary staple across this region for many Amazonian forager-horticulturalist groups ( Piperno, 2011 ). Fermented cassava beer remains a key component of the diet for many, with fermentation improving bioavailability and synthesis of essential vitamins and minerals (zinc, calcium, iron and magnesium) that may otherwise be lacking ( Boonnop et al, 2009 ; Ahaotu, Ogueke & Owuamanam, 2011 ; Dilworth, Brown & Asemota, 2013 ). This is particularly important since chronic nutritional stress among indigenous groups can stunt growth ( Blackwell et al, 2009 ; Piperata et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we associated the uptake of the major mineral targets zinc and calcium into the edible root crop with root phenotypes. Both mineral concentrations in cassava are associated with bioavailability to humans of 12%–15% in processed and unprocessed form (Dilworth et al., 2013; Narayanan et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Lower birth weight and height are known indicators of growth stunting associated with deficiencies in the micronutrients calcium and zinc (Branca & Ferrari, 2002). Cassava is a staple root crop in Thailand (Nandagopal & Syeda, 2018) and previous studies reported that micronutrient concentration in cassava correlates with bioavailability of micronutrients to the human body (Dilworth, Brown, Brown, & Asemota, 2013). In response, we asked if higher micronutrient concentrations of calcium and zinc are achievable by integrating high‐throughput root phenotyping into breeding and selection pipelines for cassava.…”
Section: Introductionmentioning
confidence: 99%
“…First domesticated in neo-tropical lowland South America 8000-10,000 years ago, cassava continues to be a dietary staple across this region for many Amazonian foragerhorticulturalist groups (Piperno, 2011). Fermented cassava beer remains a key component of the diet for many, with fermentation improving bioavailability and synthesis of essential vitamins and minerals (zinc, calcium, iron and magnesium) that may otherwise be lacking (Boonnop et al, 2009;Ahaotu et al, 2011;Dilworth et al, 2013). This is particularly important since chronic nutritional stress among indigenous groups can stunt growth (Blackwell et al, 2009;Piperata et al, 2011).…”
Section: Introductionmentioning
confidence: 99%